2016
DOI: 10.2196/resprot.5897
|View full text |Cite
|
Sign up to set email alerts
|

Securing the Continuity of Medical Competence in Times of Demographic Change: A Proposal

Abstract: BackgroundUniversity hospitals make up the backbone of medical and economic services of hospitals in Germany: they qualify specialist physicians, ensure medical research, and provide highly specialized maximum medical care, which other hospitals cannot undertake. In addition to this assignment, medical research and academic teaching must be managed despite a growing shortage of specialist physicians. By the year 2020, the need for the replacement of retired physicians and increased demand will total 30,000 pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
2

Relationship

3
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Interviews and survey carried out within the "FacharztPlus" project (further referred to as PhysicianPlus), a project financially supported by the German Ministry of Education and Research (BMBF) and aiming towards finding measures in order to retain physicians in hospitals. (Hasebrook et al, 2016a) Physicians from German university hospitals, residents and physicians, in 15 departments of anesthesiology were interviewed and surveyed. (Hinkelmann et al, 2017) The results were used to evaluate measures to increase job satisfaction in other industries, which have to deal with shift work, a need for an adaptive and at least partly highly qualified workforce, such as professional services, harbor and airport logistics.…”
Section: Project Background and Research Questionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interviews and survey carried out within the "FacharztPlus" project (further referred to as PhysicianPlus), a project financially supported by the German Ministry of Education and Research (BMBF) and aiming towards finding measures in order to retain physicians in hospitals. (Hasebrook et al, 2016a) Physicians from German university hospitals, residents and physicians, in 15 departments of anesthesiology were interviewed and surveyed. (Hinkelmann et al, 2017) The results were used to evaluate measures to increase job satisfaction in other industries, which have to deal with shift work, a need for an adaptive and at least partly highly qualified workforce, such as professional services, harbor and airport logistics.…”
Section: Project Background and Research Questionsmentioning
confidence: 99%
“…The 14 items PhysicianPlus job satisfaction scale had a satisfactory reliability of Cronbach's alpha = 0.78. In other preliminary studies the PhysicianPlus scale which is based on the well-known employees promotor scale was already used in the same setting (Hasebrook et al, 2016b;Hinkelmann et al, 2017;Hahnenkamp et al, 2018) but also in different settings such as the project "rural/rescue". (Hasebrook et al, 2022) Here, the scale was found to be highly reliable with an Cronbach's Alpha of 0.91 while in prior studies in the same present setting, the reliability was examined to lay at 0.78.…”
Section: Physicianplus Satisfaction Scalementioning
confidence: 99%
“…It is important that job requirements and work resources are balanced [53]. Based on extensive preliminary studies published elsewhere [54][55][56], we combined these aspects in a polarity profile, which includes questions to be scored from 1 (positive pole) to 10 (negative pole; see table 2). An example question concerning support from colleagues reads as follows: "For my work I get sufficient appreciation and support from my colleagues" (positive pole=1) or "My work is not appreciated and unnecessarily criticized by my colleagues" (negative pole=10).…”
Section: Methodsmentioning
confidence: 99%
“…Our project brings together novel research and innovative implementation methods, which have not yet been applied to GEP or gender action plans in health care. Nonetheless, all research and implementation methods are scientifically sound and have been proven to work in projects of consortium members, such as the German FacharztPlus project [ 28 ].…”
Section: Methodsmentioning
confidence: 99%